2022
DOI: 10.1039/d2ta02237k
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of layered materials to ultrathin amorphous nanosheets induced by ball-milling insertion and pure-water exfoliation

Abstract: A simple and universal two-step strategy, “ball-milling insertion and pure-water exfoliation”, to efficiently produce high quality ultrathin amorphous 2D nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Cathodic exfoliation is typically performed in organic solvents such as dimethyl sulfoxide (DMSO). 18–64 El Garah et al presented a rapid (<1 hour) electrochemical exfoliation method for molybdenum disulfide (MoS 2 ) using lithium-ion intercalation, with a lithium chloride solution in DMSO as the electrolyte. Their results pave the way for a rapid and ambient condition preparation of MoS 2 nanoflakes with an average lateral size of about 0.8 μm, suitable for low-cost electronic (optoelectronic) devices.…”
Section: Synthesis Methods Of Molybdenum Disulfidementioning
confidence: 99%
See 3 more Smart Citations
“…Cathodic exfoliation is typically performed in organic solvents such as dimethyl sulfoxide (DMSO). 18–64 El Garah et al presented a rapid (<1 hour) electrochemical exfoliation method for molybdenum disulfide (MoS 2 ) using lithium-ion intercalation, with a lithium chloride solution in DMSO as the electrolyte. Their results pave the way for a rapid and ambient condition preparation of MoS 2 nanoflakes with an average lateral size of about 0.8 μm, suitable for low-cost electronic (optoelectronic) devices.…”
Section: Synthesis Methods Of Molybdenum Disulfidementioning
confidence: 99%
“…They also demonstrated that this method enabled the production of a series of amorphous 2D nano-materials with heterostructures composed of two or more components and multiple interfaces, with a yield of up to 97.5%. 20 Liu and Kumatsu proposed a simple and effective alternative to produce MoS 2 and WS 2 nanoflakes using sodium cholate as a surfactant during the milling process to facilitate exfoliation and dispersion of the nanoflakes in water. They showed that the exfoliated sample can be stored as a “solid stock” and easily dispersed in water by manual agitation, resulting in highly concentrated dispersions of MoS 2 and WS 2 nanoflakes with yields reaching 93% and 57%, respectively, after centrifugation.…”
Section: Synthesis Methods Of Molybdenum Disulfidementioning
confidence: 99%
See 2 more Smart Citations